Desain Pengembangan Sistem Pembelajaran Online Berbasis Kehadiran Sosial (Sosial Presence) - Rusdiana, Ika; Aini, Shofwatul (LP. Ma'arif Janggan Magetan, 2024)
This study aims to develop an online learning system (LMS) based on social presence. Through the innovation of this system, it is expected to create a new, more interactive atmosphere in online learning, facilitating interaction and engagement among learners. Social presence is a key element in creating an effective and meaningful online learning experience. It refers to the learners' ability to feel present, connected, and emotionally as well as socially engaged in the online learning environment. This study adopts a development research approach using the ADDIE model. The product of this research is a Learning Management System (LMS) accessible at www.goocid.com. GOOCID stands for Go Online Class in Indonesia. The results of product feasibility testing by experts indicate a feasibility level of 80%, meaning that this LMS offers high-quality UI (User Interface) and UX (User Experience) that meet user needs. Moreover, psychological experts' evaluations of the